2018
DOI: 10.1111/nbu.12354
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota and cardiovascular health benefits: A focus on wholegrain oats

Abstract: Existing scientific data suggest that a high intake of wholegrain foods contributes to improved gut health and a reduced risk of cardiovascular disease. Wholegrain oats are rich in dietary fibre and an important source of many bioactive components, including minerals, vitamins and phenolic compounds. The oat b-glucans have been reported to lower low-density lipoprotein cholesterol through their ability to increase the viscosity of intestinal chime, change the gut microbiota composition and increase the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 184 publications
0
9
0
1
Order By: Relevance
“…The gut microbiota is a complex ecosystem inhabiting in the gastrointestinal tract and consisting of a diverse microbiotic community living in symbiosis with the host [ 1 ]. Mounting studies have suggested that the gut microbiota possesses many vital functions, functioning as an indispensable part of the human body to maintain our health, including regulating the energy metabolism, immune function, and hormonal balance [ 2 , 3 , 4 ]. The gut microbiota can directly shape our health states.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is a complex ecosystem inhabiting in the gastrointestinal tract and consisting of a diverse microbiotic community living in symbiosis with the host [ 1 ]. Mounting studies have suggested that the gut microbiota possesses many vital functions, functioning as an indispensable part of the human body to maintain our health, including regulating the energy metabolism, immune function, and hormonal balance [ 2 , 3 , 4 ]. The gut microbiota can directly shape our health states.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that portions of modified dishes contained significantly more dietary fibre, fat, protein, and total carbohydrates in comparison to the traditional versions (Supplementary Table S1). Dietary fibre is an essential component of the human diet due to its health benefits [23,24,25]. Călinoiu and Vodnar [26] showed that wholegrain flour products have excellent nutritional properties due to their pro-health nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Beta‐glucans can also positively influence glycaemic index levels and have a prebiotic effect by increasing the diversity of bacterial strains in the gut microbiota (Jayachandran et al ., ; Makki et al ., ). They are classed as a pre‐pharmacological interventions based on their serum lipid lowering capabilities, positive effect on lowering the risk of diabetes and reducing cardiovascular risk factors (Kristek et al ., ; Wang et al ., ; Wolever et al ., ).…”
Section: Evolution Of the Meaning Of Functional Foodmentioning
confidence: 99%